Software-defined radio technology (Roles and Simulation) - Chua, T.C (University Malaysia Sarawak, (UNIMAS), 2003)
In a software defined radio, functions that were formerly carried out solely in hardware such as the generation of the transmitted signal ans tuning and detection of the received radio signal are performed by software and controls high-speed signal processors. Because of the ability to be easily reprogrammed, a SDR could be programmed easily to operate over a broad range of frequencies, bandwidth and transmission standard. This reprogramming capability could allow a single device to transmit in the various cellular and broadcast services worldwide. This project is to study the role of SDR technologies for the future wireless system with some possible simulation.